2020
DOI: 10.31219/osf.io/jghdn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Curcumin and Colon Cancer

Abstract: Curcumin, derived from turmeric (Curcuma longa) has been extensively studied andvalued for its anti-cancer properties. It acts against a wide range of cancers by hindering the sixmain traits of all cancers, and the most prominent mechanisms include targeting inflammatorypathways. However, since curcumin has low bioavailability, most of it is excreted causing lowsystemic levels, but measurable concentrations in the colonic mucosa. Consequently, colon cancer,which has a high rate of incidence, is one of the more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…P.V. Badiger et al [6] studied the influence of cutting parameters on cutting forces, tool wear and surface roughness in hard turning using coated carbide tools. The obtained results indicated that AlCN/AlC coatings exhibited lower cutting force and better surface quality than Nguyen Phu Son, ETJ Volume 09 Issue 04 April 2024…”
Section: Application Of Coated Carbide Tools In Hard Turningmentioning
confidence: 99%
See 1 more Smart Citation
“…P.V. Badiger et al [6] studied the influence of cutting parameters on cutting forces, tool wear and surface roughness in hard turning using coated carbide tools. The obtained results indicated that AlCN/AlC coatings exhibited lower cutting force and better surface quality than Nguyen Phu Son, ETJ Volume 09 Issue 04 April 2024…”
Section: Application Of Coated Carbide Tools In Hard Turningmentioning
confidence: 99%
“…In addition, the lower cutting forces and cutting temperature were reported in case of using coated carbide tool. Pradeep V Badiger et al [6] TiN/MT TiC,N/Al2O3 coated carbide The tool wear increased with the higher cutting speed. The main wear mechanism is abrasive wear.…”
Section: Reference and Yearmentioning
confidence: 99%